2011
DOI: 10.1007/s00192-011-1428-x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training for treatment of pelvic organ prolapse: an assessor-blinded randomized controlled trial

Abstract: PFMT is effective in the treatment of pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 20 publications
3
48
0
6
Order By: Relevance
“…All three reported significantly fewer prolapse symptoms in the PFMT group compared to the control group at follow-up. Two of three reported significantly more women with decreased POP-Q stage in the intervention group compared to control; [38,39] while the third trial also found a trend in this direction. [36] Based on previous studies and new evidence from four new trials, PFMT may improve the symptoms of prolapse and the anatomical defects (Level of Evidence: 1).…”
Section: (22) Physical Therapies For Popmentioning
confidence: 84%
“…All three reported significantly fewer prolapse symptoms in the PFMT group compared to the control group at follow-up. Two of three reported significantly more women with decreased POP-Q stage in the intervention group compared to control; [38,39] while the third trial also found a trend in this direction. [36] Based on previous studies and new evidence from four new trials, PFMT may improve the symptoms of prolapse and the anatomical defects (Level of Evidence: 1).…”
Section: (22) Physical Therapies For Popmentioning
confidence: 84%
“…After 14 weeks, the intervention group showed significant improvement in relation to control group and also the decrease of symptoms. Besides, it presented with increased strength and muscular resistance and better electromyography parameters than the control group 14 …”
Section: Resultsmentioning
confidence: 89%
“…Studies have also demonstrated an improvement in associated stress urinary incontinence following pelvic floor muscle training [37,39,42]. It should be noted, however, that in these studies the correct pelvic floor contraction was determined by the physiotherapist by means of palpation.…”
Section: Pelvic Floor Muscle Trainingmentioning
confidence: 94%
“…Several randomized studies have shown that targeted pelvic floor muscle training can reduce the symptoms of prolapse, lower the grade of prolapse, and prevent progression [36][37][38][39][40][41]. Studies have also demonstrated an improvement in associated stress urinary incontinence following pelvic floor muscle training [37,39,42].…”
Section: Pelvic Floor Muscle Trainingmentioning
confidence: 99%